Study on application-oriented evaluation method for stealth materials - CUI Yiwen; LI Peishan; MA Lianfeng; ZHOU Hai (Hangkong gongcheng jinzhan)
The performance verification and evaluation of stealth materials are a crucial part in the research & development（R&D）and application cycle of high-performance stealth materials. In order to solve the problems such as single content and incomplete evaluation method of stealth materials，a new evaluation method for application-oriented stealth materials is proposed. The method improves the shape of the test specimen to weaken the interference of the non-examination scattering source on the test results as much as possible. In addition，the area integration method is further utilized to weight the area integration of the test data in multiple bands，and a comprehensive quantitative evaluation is made on the key performance of stealth materials. This method has been applied in the optimization process of stealth materials for a typical stealth combat aircraft，and practice has shown that：the method is oriented to practical engineering needs，fully characterizes the key stealth performance of stealth materials in practical application scenarios. It has the characteristics of comprehensive and accurate evaluation，providing a new approach for the comprehensive evaluation of the key absorption performance of stealth materials in all frequency bands.